Numerical investigation on the performance analysis of thermophotovoltaic by using COMSOL - Hamzaw, Amjad H; Abed, Qahtan A (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The photovoltaic solar collector (PV) works to provide electricity in normal weather conditions. This paper displays the ﬂat plate PV/T collector produces electricity and thermal energy in overheating weather conditions. In this type of weather conditions, the intermediate efficiency of photovoltaic panels often drops. This occurs because the majority of the solar radiation that is absorbed by the PV panels is converted into heat causing them to operate at a high temperature. This result in reduced PV lifespan and intermediate efficiency. As a result, it has become necessary to use a variety of approaches to try and reduce its working temperature. The performance of PV/T solar collectors using an active air collector was implemented in the resent study. The COMSOL Multiphysics software simulation was used to investigate the effectiveness of the PV/T system. The findings of the simulation-based analysis demonstrated that the chosen model is the most successful in comparison to the model with no cooling. A Solar collector with porous metal was implemented in to reduce the PV temperature. According to the results of the numerical simulation, the metal grating's ideal angle of inclination with the horizon is 45 degrees, with a 20 mm increase in its contact area with the rear cell surface.